Wild things! : acts of mischief in children's literature - Bird, Betsy; Danielson, Julie; Sieruta, Peter D. (Sommerville, Massachusetts : Candlewick Press, 2014)
Did Laura Ingalls cross paths with a band of mass murderers? Why was a Garth Williams bunny tale dubbed "integrationist propaganda"? For adults who are curious about children's books and their creators, here are the little-known stories behind the stories. A treasure trove of information for a student, librarian, new parent, or anyone wondering about the post-Harry Potter book biz, Wild Things! draws on the combined knowledge and research of three respected and popular librarian-bloggers. Told in affectionate and lively prose, with numerous never-before-collected anecdotes, this book chronicles some of the feuds and fights, errors and secret messages found in children's books and brings contemporary illumination to the warm-and-fuzzy bunny world we think we know. Secret lives, scandalous turns, and some very funny surprises -- these essays by leading kids' lit bloggers take us behind the scenes of many much-loved children's books.
Wild things!: acts of mischief in Children's literature -- "There should not be an "should" in art": subversive children's literature -- GLBT and literature for youth: how far we've come -- Banning on their minds -- Behind-the-scenes interlude: Some hidden delights of children's literature -- Kids love 'em, critics hate 'em... and vice versa -- And to think that I saw it on Hollywood Boulevard: the celebrity children's book craze -- Behind-the-scenes interlude: Sex and death -- From mainstream to Wall Street: children's books in a post-Potter world.
Includes bibliographical references (pages 243-264) and index.
Keywords: Children's literature, English -- History and criticism; Children -- Books and reading -- English-speaking countries